Design and application of a mobile nursing trolley (一种新型一体化移动护理推车的设计与应用) - RAN Maomei (冉茂梅); GUO Xue (郭雪); TANG Xuxia (唐绪霞); CHEN Xia (陈夏) (中西医结合护理)
Improvement of medical equipment’s’ function may contribute to the efficiency of nursing care in the general hospital. This paper introduced the design and application of a mobile nursing trolley, which consisted of a mobile computer and a medical trolley. The mobile nursing trolley has been designed to enable nurses to search patient’s information and provide nursing service more efficiently. (大型综合医院住院患者多, 护理工作量大, 通过改进相关设施, 有助于提升护理工作效率。本文介绍一种新型一体化移动护理推车, 由移动电脑一体机、护理治疗推车两大部分组成, 便于护理人员及时查询患者资料和提供护理服务。)